2021
DOI: 10.1177/8755293020981981
|View full text |Cite
|
Sign up to set email alerts
|

Intensity and damage statistics of the September 19, 2017 Mexico earthquake: Influence of soft story and corner asymmetry on the damage reported during the earthquake

Abstract: A destructive intraslab earthquake occurred in Mexico City on September 19, 2017 (Mw 7.1), causing significant damage and hundreds of human losses not only in the epicentral area, but also in the States of Morelos, Puebla, Mexico and in Mexico City. Only in Mexico City itself, around 230 people died, and more than 40 buildings collapsed. The intensities recorded in some lakebed areas of the city, especially in zones with soil periods around 1.5 s, were relatively high, even surpassing spectral values of 1.0 g;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The 2017 building damage was cited as an example of the large amount of data available after an intense earthquake, not as a motivation for the paper . There is no correlation whatsoever between the conclusions offered in Reinoso et al (2021) and the main goal of the paper . The soft first story and corner asymmetry are not the targets of the paper .…”
Section: Commentmentioning
confidence: 86%
See 1 more Smart Citation
“…The 2017 building damage was cited as an example of the large amount of data available after an intense earthquake, not as a motivation for the paper . There is no correlation whatsoever between the conclusions offered in Reinoso et al (2021) and the main goal of the paper . The soft first story and corner asymmetry are not the targets of the paper .…”
Section: Commentmentioning
confidence: 86%
“… (3) The authors wrote that “after the 17 September 2017 earthquake, more than 15,000 buildings in Mexico City were reported to have some type of damage,” which motivated their proposal. According to the statistics reported by Reinoso et al (2021), buildings built before 1985 and having soft story as well as corner asymmetry were particularly vulnerable to the 2017 earthquake, and they are the target of their introduced post-earthquake assessment procedure. However, Ruiz-García and Cárdenas (2021) have shown that weak first-story reinforced concrete buildings designed prior to 1985 in Mexico City do not exhibit an elastoplastic capacity curve nor uniform lateral displacement distribution under earthquake ground motions.…”
Section: Commentmentioning
confidence: 99%
“…The authors wrote that “after the 17 September 2017 earthquake, more than 15,000 buildings in Mexico City were reported to have some type of damage,” which motivated their proposal. According to the statistics reported by Reinoso et al (2021), buildings built before 1985 and having soft story as well as corner asymmetry were particularly vulnerable to the 2017 earthquake, and they are the target of their introduced post-earthquake assessment procedure. However, Ruiz-García and Cárdenas (2021) have shown that weak first-story reinforced concrete buildings designed prior to 1985 in Mexico City do not exhibit an elastoplastic capacity curve nor uniform lateral displacement distribution under earthquake ground motions.…”
Section: Discussionmentioning
confidence: 99%
“…From the review of these studies, it has been observed that the effect of strength irregularity (weak story) on the response of the building is larger than the effect of stiffness irregularity (soft story), while the combined effect of strength and stiffness irregularities (weak and soft story) is the largest amongst all 4,6,11 . On the other hand, limited research is carried out in evaluating the seismic response of other types of vertically irregular buildings such as discontinuity in vertical elements or lateral force resisting system, 12 even though these irregularities have been the cause of severe structural damage or collapse of several buildings in the events of the past earthquake 13–16 …”
Section: Introductionmentioning
confidence: 99%
“…Further, the application of the vertical component of ground motion significantly affects the axial load demand in columns 26 . It has been reported in the analytical studies and field assessment of post‐earthquake damage that the response of buildings with discontinuities in elevation is sensitive to the effect of vertical ground motions 16,26,33–35 . Therefore, this study evaluates the seismic response of multistory 3‐dimensional (3D) RC frame buildings with discontinuity in columns.…”
Section: Introductionmentioning
confidence: 99%